Procurei em mim mesmo: subjetividade, perdas e rituais no documentário contemporâneo brasileiro - Albuquerque, Edvaldo Siqueira (2019)
This research revolves around a very specific type of film: the first-person documentary. It is circumscribed with contemporary Brazilian production, in which the production and the reception of particular narratives filmed by and filming the subject themselves have intensified in the country. Unlike the upsurge of selfies in social networks, this documentary type is perceived here as an ineluctable work that no other filmmaker could make, except the actual author-actor of the story. Since the 1990s, authors are still groping in an effort to identify this cinematographic experience of self-representation through various designations such as "confessional film", "first-person essay", "intimate diary", "narrative of the self", "the owner of the voice", "subjective documentary", "self-listening", and "autoethnography", among many other imprecise nomenclatures. This indicates that this object is still located on malleable terrain, with little-known, murky or obscure borders. However, given the intensification of public interest in these experiences of new characters in cinema, concretely, there is justification in considering it a type of film that seeks new forms of existence of the aesthetic experience by optical media, common to both art and anthropology. This experience emulates a long objective tradition, based on knowledge about the other - alterity (both cinematographic and anthropological) through the insertion of the subject who films the film itself, interposing one on the other. Reflecting on such an imbrication involves thinking about what images are (and what they may be telling us) and what place they occupy in the contemporary context. Methodologically, through the images of the contemporary Brazilian documentary, we proceeded to analyze the experience of documentary filmmakers of the self, questioning how this type of film can transform the subjectivation of the filmmaker, traditionally placed outside the scene. By analyzing the use of these images in the construction of new narratives about the subject, this study seeks to understand the new contours of subjectivation, considering elements that permeate private and social dramas and a fictionalization of the real. Starting with aspects of the subjectivation of the individual as a researcher of the self and passing through the micropolitics of the subject's actions in the field, we reach the terrain of selfrepresentation. Considering that, juxtaposed to this, the minutia of the gaze of those who know a story intimately, new characters appear in the cinema, performing as themselves, who relate their microcosms and tragedies (conflicts, losses, absences and social dramas), and how all this summons the rituals and myths of performativity where the subjects of the documentary resemble fictional characters.